2013
DOI: 10.1002/j.2333-8504.2013.tb02319.x
|View full text |Cite
|
Sign up to set email alerts
|

EXAMINING EVIDENCE OF RELIABILITY, VALIDITY, AND FAIRNESS FOR THE SUCCESSNAVIGATOR™ ASSESSMENT

Abstract: The SuccessNavigator™ assessment is an online, 30 minute self‐assessment of psychosocial and study skills designed for students entering postsecondary education. In addition to providing feedback in areas such as classroom and study behaviors, commitment to educational goals, management of academic stress, and connection to social resources, it is also designed to predict a range of early academic outcomes. By indicating students' likely success, advisors, faculty, and staff can target their interactions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
0
22
0
2
Order By: Relevance
“…A noncognitive assessment, the SuccessNavigator ® assessment, which was designed to assist colleges in making course placement decisions, was in use at more than 150 colleges and universities in 2015. An ongoing research program provided evidence related to placement validity claims, reliability, and fairness of the measure's scores and placement recommendations (e.g., Markle et al 2013;Rikoon et al 2014).…”
Section: Construct Underrepresentationmentioning
confidence: 99%
“…A noncognitive assessment, the SuccessNavigator ® assessment, which was designed to assist colleges in making course placement decisions, was in use at more than 150 colleges and universities in 2015. An ongoing research program provided evidence related to placement validity claims, reliability, and fairness of the measure's scores and placement recommendations (e.g., Markle et al 2013;Rikoon et al 2014).…”
Section: Construct Underrepresentationmentioning
confidence: 99%
“…This assessment aids their advisors and other related staff along two primary lines. The first is initial academic course placement, where SN scale scores and predictive indices provide advisors with a more holistic picture of a student's likelihood of success than would be garnered from looking only at prior academic achievement or standardized placement tests (for detail, see Markle et al, ; Rikoon, Liebtag, Olivera‐Aguilar, Robbins, & Jackson, ). The second primary student‐level use of SN is to aid in determining students' self‐perceived psychosocial strengths as well as areas in which they may benefit from further development.…”
mentioning
confidence: 99%
“…The SuccessNavigator ® assessment (SN) is an assessment used by institutions of higher education to measure student psychosocial characteristics across four broad domains: academic skills, commitment, self-management, and social support (Markle, Olivera-Aguilar, Jackson, Noeth, & Robbins, 2013). These domains each contain two or three specific subskills.…”
mentioning
confidence: 99%
“…Prior research has demonstrated positive relationships between the expression of noncognitive or psychosocial skills and both academic success and persistence in higher education (e.g., Porchea, Allen, Robbins, & Phelps, ; Poropat, ; Robbins, Allen, Casillas, Peterson, & Le, ; Robbins et al, ; Trapmann, Hell, Hirn, & Schuler, ). Specifically, the SuccessNavigator ® assessment, created by Educational Testing Service (ETS), has also been shown to predict collegiate academic success (Markle, Olivera‐Aguilar, Jackson, Noeth, & Robbins, ; Rikoon, Liebtag, Olivera‐Aguilar, Robbins, & Jackson, ). While this body of research focuses on postsecondary outcomes, it does not diminish the importance of developing strong behavioral skills earlier in one's academic career.…”
mentioning
confidence: 99%
“…academic success (Markle, Olivera-Aguilar, Jackson, Noeth, & Robbins, 2013;Rikoon, Liebtag, Olivera-Aguilar, Robbins, & Jackson, 2014). While this body of research focuses on postsecondary outcomes, it does not diminish the importance of developing strong behavioral skills earlier in one's academic career.…”
mentioning
confidence: 99%